Implementasi Nilai-Nilai Tri Hita Karana Di Era New Normal Pada Anak Dan Remaja - Ni Putu Sasmika Dewi; Ni Luh Drajati Ekaningtyas; Ni Made Arini Arini (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
Implementation ​​of Tri Hita Karana values is an important thing to do in this new normal era, especially for children and teenagers, because currently many teenagers and children tend to be indifferent to their surroundings. Community service activities carried out in Dusun Rendang Bajur, Kecamatan Gunung Sari, Kabupaten Lombok Barat, West Nusa Tenggara aim to provide guidance to children, youth and parents regarding the importance of strengthening the values ​​of Tri Hita Karana. Community service activities are carried out with materials that are tailored to the needs and problems that occur in the community and with methods in the form of lectures, discussions, making APE, mentoring and counseling. The result of this activity is a commitment to be more active in implementing the values ​​of Tri Hita Karana in everyday life. Parents are also committed to using the learning strategies that have been given in this activity to their children so that children can easily get direct understanding from their parents regarding the values ​​of Tri Hita Karana.